Syntheses of Marine Natural Products via Matteson Homologations and Related Processes - Uli Kazmaier (Marine Drugs)
Matteson homologation, a successive extension of chiral boronic esters, is perfectly suited for the synthesis of complex molecular structures containing several stereogenic centers. The “classical version” allows the introduction of various functional groups in a 1,2-anti-configuration. The absolute configuration is determined by the choice of the chiral auxiliary, which can be used to introduce several stereogenic centers. In contrast, in Aggarwal’s lithiation-borylation strategy, new chiral auxiliary reagents must be used in each reaction step, which on the other hand allows the individual insertion of the desired stereogenic centers. Both methods have their individual advantages and disadvantages and are well suited for the synthesis of marine natural products.